(3x+5)=(8x-12)

Simple and best practice solution for (3x+5)=(8x-12) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x+5)=(8x-12) equation:



(3x+5)=(8x-12)
We move all terms to the left:
(3x+5)-((8x-12))=0
We get rid of parentheses
3x-((8x-12))+5=0
We calculate terms in parentheses: -((8x-12)), so:
(8x-12)
We get rid of parentheses
8x-12
Back to the equation:
-(8x-12)
We get rid of parentheses
3x-8x+12+5=0
We add all the numbers together, and all the variables
-5x+17=0
We move all terms containing x to the left, all other terms to the right
-5x=-17
x=-17/-5
x=3+2/5

See similar equations:

| 4x5=21 | | -j-(-2j)+5j-(-j)=-14 | | 4x-22=2x+14 | | 11+5w=-7+13w | | -16=5x-2(4x-7) | | -12w+(-5w)=17 | | -x-1=x=21 | | −7(x+4)+32=8−8x | | 2/3x+2=-x-3 | | 17k-14k-2k-1=5 | | 3x-2=O | | 2m-3(m1)=4(m+3) | | 4r+(-3r)-(-10r)+(-10r)=1 | | 3/5(t+46)=-3(2-t) | | 14b-8b-5b=18 | | 2(x-2)-32=12-6x | | -72=3w+4w-29 | | -6r-(-14r)=16 | | -n-n-6=4 | | x-8=23-9(x+9) | | 10v+4v+4v+2v-15v=20 | | 3(x+5)−3=32−2x | | 3(2-x)-2(3x-1)=20 | | 0.12(x+3000)=5160 | | 10v+4v+4v+2v−15v=20 | | -6x+4=18 | | 9x+18=110 | | 18a-6a-7a+a=18 | | 9b-7b+3b+3b=8 | | 23x+7=8 | | 14y+3y-14y=12 | | x-114=10(2x+3)-11 |

Equations solver categories